The Effects of Using Multidisciplinary Care Map in Aneurysm Patients on Length of Stay, Costs, Complications and Satisfaction of Caregiver and Multidisciplinary Team - Pongcharoen, Charoonlux; Wanjeeravilai , Rossarin; Changthong, Rungnipa; Glunsupa , Bang-on; Suwanprateep, Sameena (Journal of Nursing, Siam University, 2023)
This quasi-experimental research aimed to study the effects of using multidisciplinary care map in aneurysm patients on length of stay, costs, complications and multidisciplinary team,s and care givers, satisfaction. The study sample was composed of 60 patients diagnosed with aneurysm patients and admitted at surgical department, Choapraya Yommarraj Hospital, Suphanburi. The sample were divided into two groups: one experimental group received to care by using multidisciplinary care map in aneurysm patients and one control group received routine care). Each group consisted of 30 patients selected by a purposive sampling to meet specific requirements. With respect to the similarity between the experimental and the control groups, the patients were matched, based on the variables. The multidisciplinary team of 30 persons worked together and used care map in aneurysm patients. The research instruments were 1) the care map developed by the multidisciplinary team, 2) a record length of stay, cost and complications form, 3) the multidisciplinary team on using multidisciplinary care map in aneurysm patients satisfaction questionnaire. and 4) the care givers on using multidisciplinary care map in aneurysm patients satisfaction questionnaire. Reliability testing of the multidisciplinary team’s and the care givers, satisfaction questionnaire were computed by using Cronbach, s alpha coefficient which were .91 and .90. Data were analyzed by descriptive statistics and the independent t-test. Results of this study showed that 1) the experimental group reported statistically significant mean score length of stay(mean =15.63 day, SD=2.35) less than the control group (mean=22.60 day ,SD=6.36) (p=.01) 2) the mean score of costs in the experimental group (mean=153124.93 bath, SD=31269.35) less than the control group (mean=179560.33 bath ,SD=49663.94) (p=.01) 3)the mean score of complications the experimental group(mean= 0.10 person, SD=0.31)less than the control group (mean =0.37 person, SD=0.49) (p=.05) 4) a high level of care givers, satisfaction on using care map in aneurysm patients(mean=4.45, SD=0.43) , and 5) a high level of the multidisciplinary team, s satisfaction on using care map in aneurysm patients(mean=3.78,SD=0.32). Recommendations should using multidisciplinary care map in clipping aneurysm patients.